ASSOCIATION OF PERICORONITIS AND ANGULAR IMPACTIONS IN A PRIVATE DENTAL INSTITUTION - Karthik EVG; Murugaiyan Arun; Uma Maheshwari T.N (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
To evaluate the association of pericoronitis and angular impactions.Infection and inflammation of the pericoronal soft tissue of partially erupted mandibular third molars is the most prevalent in the younger population.The pattern of eruption of the third molars gave an impact in the development of pericoronitis. Pericoronitis, accounting approximately 10% of the reason for extraction of the third molars is a painful, debilitating infection A total of 27 subjects who underwent operculectomy procedures were chosen from the study in a total of 49,832 subjects screened for the data. All the case records and treatment records were obtained from the patient management software known as DIAS.The statistical analysis was performed using IBM SPSS ( Version - 24 ).The results showed the association of pericoronitis and angular impactions. Chi square tests were performed between age and gender to treatment modality for pericoronitis. Age,gender and type of impaction were also compared using the Chi square test. Statistical significance was set at p <0.05. A significant correlation was observed between gender, type of impaction and treatment modality.Within the limitations of the study, the most common type of impaction associated with pericoronitis is disto-angular impactions. The most commonly affected tooth was 48 and commonly affected gender was male. The frequent treatment modality chosen to treat pericoronitis was surgical operculectomy.